The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1807-7692bar2021210009
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic and Innovation in Healthcare: The End-To-End Innovation Adoption Model

Abstract: The pandemic has been a challenge for many public health systems worldwide. Several health measures and innovations have been implemented to help in reducing COVID-19 spread and to avoid healthcare system overwhelming. During the pandemic emergency, the need for social protection and social distancing scenario has provided the push for healthcare stakeholders to innovate, and telemedicine has emerged as an efficient and effective way to provide care while reducing hospital overload and COVID-19 spread. The pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…However, with the ADM strategy, is likely that a large pool of informal sector enrollees would be retained in the scheme provided their annual premiums are renewed. Such successful experiences with similar implementation features had been reported elsewhere (14,27,28).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, with the ADM strategy, is likely that a large pool of informal sector enrollees would be retained in the scheme provided their annual premiums are renewed. Such successful experiences with similar implementation features had been reported elsewhere (14,27,28).…”
Section: Discussionsupporting
confidence: 72%
“…There is limited empirical evidence on the implementation of ADM in health insurance. However, existing literature shows that an end-to-end (E2E) innovation adoption model for the telemedicine process had been implemented in COVID-19 pandemic control in Brazil ( 14 ). Evidence indicated that the E2E model yielded a faster and more efficient outcome and, consequently, an optimization of the adoption process of telemedicine innovation ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pandemi COVID-19 membuat perlunya inovasi, termasuk di sektor kesehatan, baik dalam proteksi terhadap infeksi, pelayanan dan keselamatan pasien, akses terhadap pelayanan, maupun pada strategi pemasaran. Pandemi COVID-19 juga menjadi katalisator pertumbuhan solusi inovatif, khususnya berupa perkembangan teknologi digital (10).…”
Section: Pembahasanunclassified
“…Innovation can be considered preventive when it has future benefits or when it intends to avoid a negative consequence (Overstreet et al, 2013). Adopting telemedicine (Guarcelo & Raupp, 2021) and masks to prevent the spreading of COVID-19 (Howard et al, 2021) exemplify the second case. Rogers (1988; argues that there are three main obstacles to adopting preventive innovation: generally, the motivation to adopt is not related to profit, there is often a need for professional training before the adoption, and future-only benefits can discourage early adopters.…”
Section: Theoretical Background and Proposed Hypotheses Preventive An...mentioning
confidence: 99%